Artifacts by Misalignment of Cardiac Magnetic Resonance Phased-array Coil Elements: From Simulation to In vivo Test - De Marchi, Daniele; Flori, Alessandra; Martini, Nicola; Giovannetti, Giulio (Current Medical Imaging, 2019)
Background: Cardiac magnetic resonance evaluations generally require a radiofrequency coil setup comprising a transmit whole-body coil and a receive coil. In particular, radiofrequency phased-array coils are employed to pick up the signals emitted by the nuclei with high signal-tonoise ratio and a large region of sensitivity. Methods: Literature discussed different technical issues on how to minimize interactions between array elements and how to combine data from such elements to yield optimum Signal-to-Noise Ratio images. However, image quality strongly depends upon the correct coil position over the heart and of one array coil portion with respect to the other. Results: In particular, simple errors in coil positioning could cause artifacts carrying to an inaccurate interpretation of cardiac magnetic resonance images. Conclusion: This paper describes the effect of array elements misalignment, starting from coil simulation to cardiac magnetic resonance acquisitions with a 1.5 T scanner. Phased-array coil simulation was performed using the magnetostatic approach; moreover, phantom and in vivo experiments with a commercial 8-elements cardiac phased-array receiver coil permitted to estimate signal-to-noise ratio and B1 mapping for aligned and shifted coil.
Keywords: MRI artifacts